Distributed Order Scheduling and its Application to Multi-Core DRAM Controllers - Moscibroda, Thomas; Mutlu, Onur (27th Annual Symposium on Principles of Distributed Computing (PODC), 2008)
We study a distributed version of the order scheduling problem that arises when scheduling memory requests in shared DRAM systems of many-core architectures. In this problem, a set of n customer orders needs to be scheduled on multiple facilities. An order can consist of multiple requests, each of which has to be serviced on one designated facility, and an order is completed only when all its requests have been serviced. In the distributed setting, every facility has its own request buffer and must schedule the requests having only limited knowledge about the buffer state at other facilities. In this paper, we quantify the trade-off between the amount of communication among different facilities and the quality of the resulting global solution. We show that without communication, the average completion time of all orders can be by a factor (√n) worse than in the optimal schedule. On the other hand, there exists a 2-approximation algorithm if the complete buffer states are exchanged in n communication rounds. We then prove a general upper bound that characterizes the region between these extreme points. Specifically, we devise a distributed scheduling algorithm that, for any k, achieves an approximation ratio of O(k) in n/k communication rounds. Finally, we empirically test the performance of our different algorithms in a many-core environment using SPEC CPU2006 benchmarks as well as Windows desktop application traces.
PODC Best Presentation Award